2018
DOI: 10.3390/cancers10100351
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Bortezomib and Menadione Sodium Bisulfite on Proteasomes of Tumor Cells: The Dramatic Decrease of Bortezomib Toxicity in a Preclinical Trial

Abstract: Tumor growth is associated with elevated proteasome expression and activity. This makes proteasomes a promising target for antitumor drugs. Current antitumor drugs such as bortezomib that inhibit proteasome activity have significant side effects. The purpose of the present study was to develop effective low-toxic antitumor compositions with combined effects on proteasomes. For compositions, we used bortezomib in amounts four and ten times lower than its clinical dose, and chose menadione sodium bisulfite (MSB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Nonetheless, the present data also suggest caution should be applied in the use of these CGs in normal cells, and disclose the necessity to accurately choose concentrations of OU and Digo, and control their effects on the proteasome during the developmental phase of a CGs-based pharmacological treatment. Indeed, although we demonstrated that OU and Digo do not activate the proteasome in a non-transformed cell line, available data show that high proteasome activity relates to cancer development [ 56 , 57 ]. However, at the same time, our data strongly indicate that the OU and Digo ability to activate the proteasome is prospective for the treatment of ERα-expressing BCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the present data also suggest caution should be applied in the use of these CGs in normal cells, and disclose the necessity to accurately choose concentrations of OU and Digo, and control their effects on the proteasome during the developmental phase of a CGs-based pharmacological treatment. Indeed, although we demonstrated that OU and Digo do not activate the proteasome in a non-transformed cell line, available data show that high proteasome activity relates to cancer development [ 56 , 57 ]. However, at the same time, our data strongly indicate that the OU and Digo ability to activate the proteasome is prospective for the treatment of ERα-expressing BCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer stem cells are characterized by decreased proteasome activity and increased resistance to proteasome inhibitors (293), indicating that the improvement of inhibitor-based therapeutic approaches is necessary. Indeed, combinations of inhibitors with different molecules decreased the active dose required and increased inhibitor potency (283, 284). Different proteasome forms found in cancer cells are involved in the immune recognition of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, bortezomib is known for strong side-effects that limit its clinical use. To decrease the side-effects and increase the efficacy combinations of bortezomib with other molecules were proposed (283, 284). (B) Subunit specific inhibitors allowed targeting specific subsets of proteasomes and especially iP subunit-specific inhibitors are considered very useful against certain autoimmune disorders and inflammation-induced tumors (90, 91).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib (BTZ) was the first proteasome inhibitor to be developed and is mainly used to treat hematologic tumors, such as multiple myeloma and small cell lymphoma . However, its usefulness for solid tumor therapy is limited owing to its poor stability and toxicity in vivo …”
Section: Introductionmentioning
confidence: 99%